Analisis Kinerja Humas pada Marketing Kegiatan Open House Politeknik Pariwisata Prima Internasional - Yuke Hernawati,; Joseph Aldo Irawan,; Abdul Khalim,; Moch. Rizky Najmuddin,; Chondro Suryono, (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
In organizing an activity, of course, it requires the role of public relations as a connector of information to the community. Public relations from the Prima International Tourism Polytechnic made several efforts in socializing open house activities. Socialization both through digital content, e-brochures to visits to schools conventionally. Through a descriptive participative method and filling out questionnaires, random sampling was carried out and a total of 130 respondents were found. Assisted by field observation and documentation activities, data interpretation can be done more clearly and in detail. In some questionnaire questions found positive results and based on these results, it can be assessed the performance process of public relations that can exceed the expectations of management. There are several things that can still be improved in the future so that open house activities by the Prima International Tourism Polytechnic are more mature in the process of implementation.